Estimating local administrators' participation in planning: Case of "Egypt vision 2030" - Heba Saleh Moghaieb (Review of Economics and Political Science (REPS), 2019)
Purpose - This paper aims to address to what extent local administration is involved in national planning focusing on drafting and reviewing processes of "Egypt Vision 2030". Design/methodology/approach - The paper plan to use focus group discussions and descriptive-analytical approach with representatives of local administration in three governorates. Findings - Importance of local participation is not any more a question; however, participation concept and methodology are what matters. Participatory approach is not complex-free. It is crucial to consider conflicts of interest groups, ideologies, and political trends, communities' high expectations, particularly of those who were marginalized and deprived for long time. Definitions should not be unified on national, regional and local levels. Each community needs to agree on its own definitions, needs, dreams and paths toward development. Accordingly, the role of the planner is to expand choices and opportunities for each citizen. Participation in planning for the future must include the coming generation who are opting to live this tomorrow. That requires institutionalization of youth participation in the decision-making processes. Research limitations/implications - It was difficult to ensure meeting adequate sample; however, the author does believe that the participated sample represents the case. Practical implications - The impact of public participation in planning on enhancing the planning processes and strategic planning outcomes and implementation is not a matter of questioning anymore, although governments do not pay due attention. Social implications Public participation in planning processes named participative planning is crucial for achieving development, social justice, economic development and public trust in governments. Originality/value - The paper depends on focus-group discussions that were conducted by the author. Analysis and discussions reflect the author's academic and practical experiences.
Keywords: 330; Strategic planning; Egypt vision 2030; Local administration; Participatory planning; Regional planning